FRI0408 Neopterin as a serological marker of disease activity in patients with anti-melanoma differentiation-associated gene 5 antibody positive clinically amyopathic dermatomyositis. (15th June 2017) - Tsunoda, S; Nishioka, A; Abe, T; Kitano, M; Matsui, K; Sano, H
Abstract : Background: Anti-melanoma differentiation-associated gene 5 (MDA5) antibody in clinically amyopathic dermatomyositis (CADM) is associated with rapidly progressive interstitial lung disease (RPILD). RPILD is a rare disorder with a bad outcome, and therefore the intensive treatment with combinational immunosuppressive drugs in addition to steroid need to be initiated. However until now, good serological markers to evaluate disease activity in CADM have not been established. Activated alveolar macrophage is one of the possible candidates worsening the condition of RPILD. Objectives: To investigate new serological markers of disease activity in anti-MDA5 antibody positive CADM for therapeutic indication. Methods: Thirteen anti-MDA5 antibody positive CADM patients were enrolled. We serially measured serum anti-MDA5 antibody, and neopterin and IL-18 as markers of activated macrophage by serum enzyme-linked immunosorbent assay. We tracked them at three points in each patients: before treatment, soon after a series of intravenous cyclophosphamide pulse therapy (about 3months later after onset) and the remission status (about one year later after onset). Results: Four patients died soon after the initial treatment because of the deterioration of RPILD. At onset of the disease, the levels of serum anti-MDA5 antibody and neopterin were extremely high (169.75±24.3 index and 27.6±24.1 nmol/l) in all patients. However serum IL-18 level was almost normal (479.3±301.4 pg/ml). Among the 9 surviving patients, it took about one year for anti-MDA5 antibody level to decrease to the normal range. On the other hand, neopterin level decreased quickly after the initial treatment. The level of anti-MDA5 antibody transitioned from 169.75±24.3 index to 93.1±50.1 index, and then to 44.8±45.4 index (P=0.003). Neopterin level transitioned from 27.6±24.1 nmol/l to 9.1±6.5 nmol/l, and then to 6.4±5.0 nmol/l (P=0.006). IL-18 level transitioned from 479.3±301.4 pg/ml to 246.0±175.8 pg/ml, and then to 233.3±180.1 pg/ml (P=0.02). The level of anti-MDA5 didn't correlate with the level of ferritin (r=0.28), neopterin (r=0.16), IL-18 (r=0.06) and soluble IL-2 receptor (r=0.27), but the level of neopterin was well correlated with the level of ferritin (r=0.95), IL-18 (r=0.77) and soluble IL-2 receptor (r=0.75). Conclusions: Anti-MDA5 antibody titer is useful if the patients could reach and maintain the remission or not. Serum neopterin level is useful to predict the clinical status at present for therapeutic indication. References: Matsushita, et al. Br J Dermatol. 2016 Jul 25. doi: 10.1111/bjd.14882. Xu Y, et al. Clin Rheumatol. 2016, 35: 113–6. Enomoto Y et al. Arthritis Res Ther. 2017, 19:9. doi:10.1186/s13075-016-1214-8. Disclosure of Interest: None declared